A Versatile Metal‐Free Intermolecular Aminochlorination of Alkenes. Issue 1 (10th January 2014) - Martínez, Claudio; Muñiz, Kilian
Abstract New reaction conditions for the rapid and productive intermolecular aminochlorination reaction of alkenes using a combination of chloramine‐T and a Brønstedt acid are described. Upon simple protonation of chloramine‐T, conditions for a mild and selective aminochlorination are obtained. In addition, the reaction can proceed to form either of the two possible regioisomers, depending on whether a stoichiometric amount of such an acid activator or acetic acid is used as solvent. The reaction is operative for all different classes of alkenes. A total of over 50 examples is presented to illustrate this concept. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>